18F-FAZA PET/CT in pretreatment assessment of hypoxic status in high-grade glioma: correlation with hypoxia immunohistochemical biomarkers. Issue 7 (July 2021) - Mapelli, Paola; Callea, Marcella; Fallanca, Federico; Castellano, Antonella; Bailo, Michele; Scifo, Paola; Bettinardi, Valentino; Conte, Gian Marco; Monterisi, Cristina; Rancoita, Paola Maria Vittoria; Incerti, Elena; Vuozzo, Marta; et al.
Abstract : Background: To investigate the correlation between 18 F-labeled fluoroazomycinarabinoside (18F-FAZA) PET data and hypoxia immunohistochemical markers in patients with high-grade glioma (HGG). Patients and methods: Prospective study including 20 patients with brain MRI suggestive for HGG and undergoing 18F-FAZA PET/CT before treatment for hypoxia assessment. For each 18F-FAZA PET scan SUVmax, SUVmean and 18F-FAZA tumour volume (FTV) at 40, 50 and 60% threshold of SUVmax were calculated; hypoxic volume was estimated by applying different thresholds (1.2, 1.3 and 1.4) to tumour/blood ratio. Seventeen patients were analysed. The immunohistochemical analysis assessed the following parameters: hypoxia-inducible factor 1α, carbonic anhydrase IX (CA-IX), glucose transporter-1, tumour vascularity and Ki-67. Results: 18F-FAZA PET showed a single lesion in 15/17 patients and multiple lesions in 2/17 patients. Twelve/17 patients had grade IV glioma and 5/17 with grade III glioma. Bioptic and surgical samples have been analysed separately. In the surgical subgroup ( n  = 7) a positive correlation was observed between CA-IX and SUVmax ( P  = 0.0002), SUVmean40 ( P  = 0.0058), SUVmean50 ( P  = 0.009), SUVmean60 ( P  = 0.0153), FTV–40–50–60 ( P  = 0.0424) and hypoxic volume1.2–1.3–1.4 ( P  = 0.0058). In the bioptic group ( n  = 10) tumour vascularisation was inversely correlated with SUVmax ( P  = 0.0094), SUVmean40 ( P  = 0.0107), SUVmean50 ( P  = 0.0094) and SUVmean60 ( P  = 0.0154). Conclusions: The correlation of 18F-FAZA PET parameters with CD31 and CA-IX represents a reliable method for assessing tumour hypoxia in HGG. The inverse correlation between tumour vascularisation, SUVmax and SUVmean suggest that highly vascularized tumours might present more oxygen supply than hypoxia.